Development of Interactive Learning Media Assisted by Lumio by SMART to Increase The Learning Motivation of IPAS - Anike Dyah Ayu Suryandani; Sri Sami Asih (Jurnal Penelitian Pendidikan IPA, 2024)
The lack of technology utilization in the learning process at SDN Klepu 01 affects students' learning motivation. This research aims to develop interactive learning media assisted by Lumio by SMART, test the media feasibility, and test the media effectiveness in increasing IPAS learning motivation in fifth-grade students of SDN Klepu 01, Semarang Regency. The type of research used is Research and Development (R&D) with the ADDIE model. The research subjects included media experts, material experts, teachers, and fifth-grade students. The data collection techniques employed non-tests such as interviews, observation, and questionnaires. Media feasibility based on the validation of material experts and media experts obtained scores of 91,25% and 90%, respectively, in a very feasible category. Media feasibility based on teacher and student responses obtained scores of 100% and 96,5%, respectively, in a very feasible category. The effectiveness of the media to increase learning motivation, based on the results of observations by teachers, obtained an average score of 90%, which shows that student learning motivation looks very good. Based on the results of the pretest-posttest questionnaire, the effectiveness of the media in increasing learning motivation is shown by the Wilcoxon Signed Rank Test, which obtained an Asymp. Sig (2-tailed) of 0,000 <0,05 shows a significant difference, while based on the N-gain results obtained a value of 0,69 with medium category. Thus, the interactive learning media assisted by Lumio by SMART that has been developed can be declared feasible and effective in increasing IPAS learning motivation.